Synthesis and characterization of iron-based two-dimensional ferromagnets - Govindan Kutty Rajendran Nair (Nanyang Technological University, 2021)
Research and development of 2D magnetic materials are quintessential for realizing the next generation of Spintronic memory devices. Due to the advancements in big data and the Internet of things, there is a massive demand for low-power consuming data storage and processing devices. Low power-consuming data storage devices can bypass the Von Neumann bottleneck problem by realizing high-density nonvolatile memory devices. 2D ferromagnetic magnetic materials are potential candidates for fabricating spintronic memory devices such as Spin logic memory devices, magnetic tunnel junctions (MTJ) for magneto-resistive random-access memory (MRAM), etc. This project mainly focuses on establishing the direct growth of 2D ferromagnets on Si/SiO2 substrates. The growth-based research of 2D magnets is currently limited to chemical vapor transport (CVT). In the CVT process, a single crystal 2D magnet is grown in a sealed furnace over time, and then subsequent mechanical exfoliation methods are required to obtain an ultra-thin 2D magnet layer. This process is non-consistent, laborious, and requires an additional step to transfer the exfoliated material to a compatible substrate capable of device fabrication. Chemical vapor deposition (CVD) can overcome this issue by facilitating the growth of 2D magnets directly on Si/SiO2 substrates. The materials studied in this thesis are two-dimensional iron di sulfide and iron germanium telluride magnets.